Unbound Water Content From Application of Adsorption Theory - Loebenstein, William V. (J Res Natl Bur Stand A Phys Chem, 1975)
It is standard procedure to fit an applicable isotherm equation to water vapor adsorption data using the method of least squares in arriving at a value for the surface area accessible to the water molecule. The least squares technique has been extended in the present investigation to determine, in addition and simultaneously, a “best value” for the zero-humidity sample weight of the material. The application is equally valid for desorption insofar as the zero-humidity weight is concerned, although the derived value for “surface area” from desorption data will be over-estimated in the general case because of hysteresis. There is no limitation on the range of humidities since the method is not restricted to the BET equation (i.e., between 0.1 and 0.3 r.h.). In fact, good agreement with the zero-humidity points measured experimentally has been obtained even from drying curves in which the relative humidity has been confined to the region above 50 percent. An iterative method is employed in the calculations for which computer assistance is especially adaptable. Fortran IV programs are included in the appendix whose use requires no extensive computer experience. A fraction of a second in computer processing time is all that is required for each determination.